Investigating Transformative Approaches in Islamic Education Through Digital Stories to Shape the Future of Learning - Shofiyyah, Nilna Azizatus; Ulum, Miftahul; Zaelani, Moh. Ichsan (STEBIS Bina Mandiri, 2025)
This study aims to investigate innovative approaches in Islamic education through the integration of digital storytelling. The research seeks to examine how digital narratives can influence the learning process of Islamic teachings. Utilizing a qualitative literature review approach, the study explores a range of sources related to Islamic education and the role of digital storytelling technology. The findings suggest that digital stories hold considerable potential to enhance the learning experience of Islamic education, especially by actively engaging students through captivating narratives. It is anticipated that these insights will contribute to modernizing the teaching of Islamic religion, ensuring it aligns with contemporary educational advancements. The implications of this research are intended to offer practical recommendations for developing novel instructional methods that foster a more creative generation of Islamic learners, equipped with a deeper understanding of religious values.